USE OF TECHNOLOGY IN ENGLISH LANGUAGE LEARNING (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
With the advent of technology, 21st century has become the era of technology. Surely, it has become a significant part of language teaching which provides meaningful and interesting approach for language learning. Majority of EFL teachers are integrating technology into their curriculum while designing material for learning process to support learning process. The use of technology in EFL classrooms inspires students and engages them listening, reading, speaking as well as writing.